Improvement of the Electrical Performance of Outdoor Porcelain Insulators by Utilization of a Novel Nano-TiO2 Coating for Application in Railway Electrification Systems - Pichai Muangpratoom; Issaraporn Khonchaiyaphum; Wanwilai Vittayakorn (My University, 2023)
The present study aimed to develop the electrical performance of outdoor insulators using a nano-TiO2 coating for railway electrification systems. The prototype design of porcelain insulators with normal coatings and using a nano-TiO2 coating is based on IEC 60815-1. The first test was performed to measure the low-frequency flashover AC voltage under both dry and wet conditions. In addition, the other test was conducted to measure the lightning impulse critical-flashover voltage at positive and negative polarity under dry-normal and wet-contaminated conditions. X-ray diffraction (X-RD) and Scanning electron microscopy (SEM) were used to examine the micro surface and show that the nano-TiO2 coating was adhered to the surface of the outdoor porcelain insulator and exists in an amorphous state. Additionally, it was observed and discovered that scattered nano-TiO2 strengthens the glassy matrix and creates a sturdy barrier that causes flashover voltage to be reduced under conditions of high dielectric strength. Nanostructured ceramic formulations outperform ordinary porcelain in terms of breakdown voltage strength, particularly for the insulators’ low-frequency flashover performances under dry and wet test conditions. However, a significant change in the lightning impulse critical-flashover voltage characteristics is observed and is not much better when adding the nano-TiO2 coating to the porcelain insulators.
Keywords: Arc flash; High Voltage; Dielectric strength; High voltage insulation and dielectric phenomena